Strategi Branding Image dalam Pemasaran Jasa Pendidikan di Masa Pandemi Tingkat Perguruan Tinggi - Munajat, Yusuf; Ramly, Amir Tengku (Diversity: Jurnal Ilmiah Pascasarjana, 2022)
Competition between educational institutions with one another is inevitable, so marketing strategies for educational institutions is an absolute must (Afrida, 2018: 1). Marketing of educational services in new student admissions is a decisive moment for universities to try to screen students according to the required capacity. The purpose of this study is to find out, analyze, understand and assess how the influence of Branding Image and what marketing strategies are applied during the pandemic at private universities in the Bogor area. This research belongs to the type of qualitative research, while the research method used is case study research. The data collected using observation, interview, and documentation techniques. Brand Image or brand image that has been trying to convey to the wider community has been successfully accepted. For example, when people, especially students, hear the word campus abbreviation, they immediately remember that the university is a university that has affordable prices for all levels of society, has excellent facilities such as large buildings, and has good quality. Brand image in the decision making of students choosing a campus is highly considered by students, they choose this college because they consider the costs that must be incurred during college, they see a very large building, and hear recommendations from their friends that the college is a quality campus. .